OBTAINING FUNCTIONAL OILS FROM PROCESSING FRUIT WASTE - Ibragimov, A.A.; Mamazhanova, I.R.; Курбанов , Н.М. (Educational Research in Universal Sciences, 2023)
Objective. This article discusses the composition and use of natural oils obtained from the processing of fruit waste, which are a source of non-traditional oils. Methods. In our study, we tried to determine the beneficial properties of functional oils enriched with non-traditional oils used in functional nutrition, the amount of biologically active substances, macro- and microelements and their properties. We studied plant samples and their triglycerides, which are part of the chemical composition of various organs, when analyzing the composition and ratio of fatty acids, amino acids, traditional and modern physicochemical and physical methods of analysis were used: extraction, thin layer chromatography (TLC) methods. Results. The acid composition of vegetable cherry oil was studied, the presence of oleic acid 52.4 wt. % and 28.3 wt. % linoleic acid. Cherry oil mainly contains oleic acids. Conclusion. The types of fatty acids play an important role in the regulation of biological functions. Oleic acid, which is found in the largest amount in the pits of cherries, is a monounsaturated fatty acid that is quickly absorbed in the body and has a fast destructive property. Triglycerides, lipoproteins, in the human diet helps reduce cholesterol levels.